The Effect of Human Resource Development and Work Motivation on The Performance of Employees of PT. Tri Agung Nusantara - Kurniawan, Arief; Elwisam; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to analyze the effect of Human Resource Development and Work Motivation on the performance of PT. Tri Agung Nusantara. The analysis method in this study is descriptive analysis. Data analysis of several tests namely instrument tests, classical assumption tests, model feasibility tests, multiple liner analysis, and t hypothesis testing using the Statistical Product and Service Solution (SPSS) Version 23.0 program. the subject of this study was an employee of PT. Tri Agung Nusantara with a total of 80 employees with data collection method through questionnaire. The results of regression analysis in this study show a positive and significant influence on performance, which is shown in the coefficient table in the regression equation model. The results of the model feasibility test are shown with significant values shown in the ANOVA table which means that the model in this study is feasible to use based on the significant value obtained. The results of the conclusion of the hypothesis with the t-test obtained significant values on the variables of Human Resource Development and Work Motivation. So it can be concluded that the two independent variables have a significant influence on the dependent variable.